As origens das guerras culturais no Brasil: desdobramentos político-filosóficos - Santos, Alan dos (2020)
This is a research on the "cultural wars" - the conceptual definition, the birth and invention, the import of this debate into Brazil and its consequences for politics and for contemporary social conflicts. Our thesis consists of problematizing cultural wars, this new way of dividing and polarizing society, as a particular chapter in the class struggle, especially in Brazil. At first, the cultural war seems to undermine and secondary class conflicts, but then we realize that it updates this fundamental historical conflict since the emergence of capitalism. Having arisen in the United States in the transition from the 1980s to the 1990s, with James Hunter (1991 ), cultural wars have placed a moral burden on the political struggles of our time. The declaration of cultural war refers to the birth of contemporary political struggles of the 1960s, especially the policies of moral openness: legalization of drugs, sexual liberation, the discussion on abortion, the rights of homosexuals, the social movements of identity - what Conservative literature called it a "cultural revolution". ln dialogue with the works of Moretto, Ortellado and Solano (2017) and other Brazilian researchers, we defe nd the perspective that cultural wars have arrived in Brazil. Our objective is to investigate the transformation of politics into war (FOUCAUL T, 2012), and especially into cultural war (KREEFT, 2011; SCRUTON, 2014), and to map the developments of this war in our country.